Clinicopathological evaluation of Odontogenic Cysts in Maysan city in Iraq (retrospective study). (Mustansiria Dental Journal, 2018)
Iraqi populations in Maysan general hospital (Maysan -Iraq) and compare thisprevalence with other international studies.Data of this study were obtained from reports of patients diagnosed withodontogenic cysts between 2007 and 2010. Case records of patients who fit theHistological Classification of the World Health Organization (2005) were included.The following variables were analyzed: gender, age group, anatomical location andhistological type. Odontogenic cysts accounted for 90 % of all lesions biopsiedthroughout the study period. Pain feeling and clinical expansion were recorded inmost of our patients. Mean patient age was (28) years and (61%) of the patients weremales. Radicular cyst was the most prevalent histological type (28.75%), followed byodontogenic keratocyst (25%) then dentigerous cyst (23.75%). The mandible was themost prevalent site of the lesions (55%).Odontogenic cysts appear to have a distinct predilection for the male gender, thethird decade of life and are more frequent in the mandible. Awareness about theprevalence and characteristics of odontogenic cysts is important in primary diagnosisand treatment of these lesions.